Adsorption of CO/CH Mixtures in a Molecular Model of Activated Carbon through Monte Carlo Simulations - Alberto G. Albesa; Matías Rafti; José L. Vicente; Hernán Sánchez; Pablo Húmpola (Adsorption Science & Technology)
In this article, a nanoporous carbon model based on units of polyaromatic molecules with different number of rings is described. The adsorption isotherms of pure CO 2 , CH 4 and equimolar mixtures, and isosteric heat calculations on these models substrates were obtained by Monte Carlo simulations. The results were analyzed in the framework of dual process Langmuir model (DPL) and on the basis of ideal adsorption solution theory. We found that both methods predict the adsorption isotherms of mixtures based on pure components data with reasonable accuracy. It has been demonstrated that the isosteric heat and selectivity of a mixture are intimately related. The DPL model does not predict the correct numerical value of selectivities; however, it predicts the correct behaviour. This is very useful as a fast method to indicate the adsorption behaviour of mixtures.